Development of the University of the Philippines Mindanao Integrated Information Management System (UPMIIMS) web-based memo management subsystem - Badoy, Larvi Jerrick Ocsio (2009)
The application program focused on the idea of providing an alternative method of releasing memoranda among all offices on the University of the Philippines Mindanao. The study resulted in the development of the system entitled ?WEB-BASED MEMO MANAGEMENT SYSTEM?, an online application that automates the process of sending, receiving, and tracking of UP Mindanao memoranda. The system?s aim is to offer a more efficient and dependable system of releasing memos compared to the current manual distribution. The system caters to two main types of users; the administrator and the client. He client users of the system can be divided into memo-releasing users, which can both send and receive memos, or memo-receiving users, which can only receive memos. The administrator, on the other hand, manages the data in the system, while at the same time also having client privileges. The system was implemented using HTML and PHP for the front-end design and MySQL for the back-end database